Pro-Apoptotic Activity of Epi-Obtusane against Cervical Cancer: Nano Formulation, In Silico Molecular Docking, and Pharmacological Network Analysis - Omnia Hesham Abdelhafez; Islam M. Abdel-Rahman; Eman Alaaeldin; Hesham Refaat; Refat El-Sayed; Sami A. Al-Harbi; Ahmed M. Shawky; Mohamed-Elamir F. Hegazy; Alaa Y. Moustafa; Nourhan Hisham Shady (MDPI AG, 2023)
Cancer is a major disease that threatens human health all over the world. Intervention and prevention in premalignant processes are successful ways to prevent cancer from striking. On the other hand, the marine ecosystem is a treasure storehouse of promising bioactive metabolites. The use of such marine products can be optimized by selecting a suitable nanocarrier. Therefore, epi-obtusane, previously isolated from Aplysia oculifera, was investigated for its potential anticancer effects toward cervical cancer through a series of in vitro assays in HeLa cells using the MTT assay method. Additionally, the sesquiterpene was encapsulated within a liposomal formulation (size = 130.8 ± 50.3, PDI = 0.462, zeta potential −12.3 ± 2.3), and the antiproliferative potential of epi-obtusane was investigated against the human cervical cancer cell line HeLa before and after encapsulation with liposomes. Epi-obtusane exhibited a potent effect against the HeLa cell line, while the formulated molecule with liposomes increased the in vitro antiproliferative activity. Additionally, cell cycle arrest analysis, as well as the apoptosis assay, performed via FITC-Annexin-V/propidium iodide double staining (flow cytofluorimetry), were carried out. The pharmacological network enabled us to deliver further insights into the mechanism of epi-obtusane, suggesting that STAT3 might be targeted by the compound. Moreover, molecular docking showed a comparable binding score of the isolated compound towards the STAT3 SH2 domain. The targets possess an anticancer effect through the endometrial cancer pathway, regulation of DNA templated transcription, and nitric oxide synthase, as mentioned by the KEGG and ShinyGo 7.1 databases.